Pengendalian Hama Kutu Daun Coklat pada Tanaman Cabe mengggunakan Pestisida Organik Ekstrak Serai Wangi: The Control of Brown Leaves Insects’ Pests (Toxoprera citricidus Kirk) on Chili (Capsicum annum L.) by Using Organic Pesticide Citronella Extract (Cymbopogon nardus L.) - Arfianto, Fahruddin (Anterior Jurnal, 2016)
Cultivation of chili is a farming activity promising an interesting profits and the market demand for the chili is high. Many chili farmers in controlling pests use chemical pesticides because it is considered more efficient and fast, actually the chemical pesticides do not kill insects’ pests, but it creates a new form of defense for insects’ pests. In another effort to find alternative pesticides are expected to be more lenient, then developing the manufacture of pesticides made from natural materials exist around the neighborhood, known by name "botanical pesticide" or "organic pesticide", because of almost all the ingredients derived from plants. The purpose of this study was to control brown leaves insects’ pests on chili by using citronella extract. The time in doing this study was as long as from October to November 2016. The study was done on Jl. Meranti IV Panarung Village, District Pahandut, the city of Palangka Raya. From the results of the experiment of several concentration of extract of citronella 25 ml, 50 ml and 75 ml and 100 ml mixed with clean water for pest control of brown leaves insect on the chili, factually, by using concentration of citronella extract of 75 ml and 100 ml mixed with clean water, it can be reducing brown leaves insects’ pest.